Performance Enhancement of P3HT: ZnO Solar Cells by Incorporating Metal Oxide Fe2O3 Nanoparticles - Dheyab, Raed A.; Hussein, Abdullah A.; Saeed, Asrar Abdulmunem (Iraqi Journal of Science, 2021)
The ferric oxide nanoparticles (Fe2O3) which are deposited at interface which is related to hole collecting buffer layer [poly(3,4-ethyl-enedioxythiophene): poly(styrene-sulfonate) (PEDOT: PSS)] as well as regioregular poly(3-hexyl-thiophene): Zinc oxide nanoparticles (P3HT): (ZnO) active layer have been considerable increasing the performance of solar cell. Also, the solar cell devices have been fabricated with a weight ratio of 1:0.7, 1:0.8, 1:0.9 and 1:1 of P3HT and ZnO, respectively. In addition, photo physical characteristics regarding such devices with different value of the weight ratio were examined. This work is indicating that the absorption spectrum related to blend will be broad with varying ratios that was extremely required for the devices of the organic solar cells. Furthermore, the film morphology was estimated via atomic force microscope (AFM). EQE (i.e. External quantum efficiency) and XRD patterns measures were achieved for the optimal device, while the improvement in the efficiency with regard to a device with 1:1 was more considerable compared to 1:0.90, 1:0.80 as well as 1:0.70 values of weight ratio of P3HT and ZnO. With different weight ratio values, a solar cell upon (1:1) provides PCE (i.e. Power Conversion Efficiency) of 4.1%, dissimilar to 3.92% for (1:0.9), 3.9% for (1:0.8) and 3:6% devices.